Extraordinary variability in gene activation and repression programs during gonadal sex differentiation across vertebrates - Sánchez-Baizán, Núria; Jarne-Sanz, Ignasi; Roco, Álvaro S.; Schartl, Manfred; Piferrer, Francesc (Frontiers in Cell and Developmental Biology, 2024)
Genes involved in gonadal sex differentiation have been traditionally thought to be fairly conserved across vertebrates, but this has been lately questioned. Here, we performed the first comparative analysis of gonadal transcriptomes across vertebrates, from fish to mammals. Our results unambiguously show an extraordinary overall variability in gene activation and repression programs without a phylogenetic pattern., During sex differentiation, genes such as dmrt1, sox9 amh, cyp19a and foxl2 were consistently either male-or female-enriched across species while many genes with the greatest expression change within each sex were not. We also found that downregulation in the opposite sex, which had only been quantified in the mouse model, was also prominent in the rest of vertebrates. Finally, we report 16 novel conserved markers and 11 pathways. We propose viewing vertebrate gonadal sex differentiation as a hierarchical network, with conserved hub genes alongside less connected and less conserved nodes. This framework implies that evolutionary pressures may impact genes based on their level of connectivity.